BENEFIT DARI PENERAPAN KURIKULUM MERDEKA - Vachry Dhani Vachry; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
The curriculum is an important tool or guide in carrying out an education. The use of the new curriculum in the world of education certainly takes time to adjust. Now in Indonesia a new independent curriculum has been implemented, where this curriculum focuses on essential material, teachers and students are flexible in learning, and project and character based. Writing this article using qualitative research with a descriptive approach. Data collection was carried out by means of a literature study. The results of the study found that there were advantages to implementing an independent curriculum from the previous curriculum. The independent curriculum is designed to make learning simpler and more in-depth. In developing it, schools and teachers are given the power in accordance with the name independence. This form of project-based learning can increase student activity and be interactive. Emphasis on character values ​​with the name Pancasila student profile consisting of faith and fear of God, independent, critical reasoning, mutual cooperation, global-minded, and creative.